Clinical and radiological follow up of post-COVID patients in tertiary care centre - Penmetsa, Chinmai Sowmya; Yalamanchili, Vijay Krishna; Yendapu, Raja Sekhar; Susmitha Pratti, Pratti Venkata Sai (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 is potentially fatal infection caused by novel corona virus SARS COV2.SARS patients may present with a spectrum of symptoms and signs ranging from relatively asymptomatic to fulminant pneumonitis and death. Out of which, most frequent symptoms are cough, fever, myalgia, dyspnoea and altered smell/taste. The primary objective of the study is to describe the clinical evolution and symptoms persistence [at day 30 and day 60] during 2 months follow up in adults with COVID-19 and to follow up the changes in lung radiographic pictures within 2 months after discharge. Methods: This is an institutional based, prospective clinical observational study conducted in Asram medical college, Eluru from September 2021 to November 2021 on 25 COVID-19 Patients. Results: In our study two thirds of patients still reported symptoms at day 30 and half of the patients reported symptoms at day 60. Out of 50 patients, 38 (76%) patients had at least one symptom at day 30 and 25 (50%) patients had symptoms at day 60 and 9 (18%) patients had chest X-ray abnormalities during follow-up after 2 months. Conclusions: Follow up studies of COVID-19 will improve our understanding of natural history of COVID-19 sequelae and enable us to assess the efficacy of therapeutic interventions to mitigate the long-term consequences of COVID-19 It is necessary to follow up these recovered patients for detection and appropriate management towards their psychological, physical and social realm. It is highly important to provide counselling, moral support to restore to normalcy.